Kontribusi Hasil Hutan Bukan Kayu (HHBK) terhadap Pendapatan Masyarakat Pengelola Hutan Kemasyarakatan (HKm) di Desa Hikong, Kecamatan Talibura, Kabupaten Sikka - Elyn Novtansya Pelupessy; Nixon Rammang; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
The utilization of Non-Timber Forest Products (NTFPs) plays an important role in increasing the income of forest-dependent communities. This study aims to determine the contribution of NTFPs to the income of community forest (HKm) farmers in Hikong Village, Talibura Sub-district, Sikka Regency. The research employed a quantitative descriptive method with purposive sampling involving 72 respondents from the HKm Tuar Tana group. Data were collected through structured interviews, observation, and documentation, and then analyzed by calculating the contribution of NTFPs to total household income, presented in the form of tables, percentages, and descriptive explanations. The results show that the community utilizes various types of NTFPs such as candlenut, cashew, areca nut, cocoa, coffee, clove, and others. The total income from NTFPs reached IDR 1,060,462,000/year with an average of IDR 14,728,639/person/year, while the average total income from all sources was IDR 16,416,764/person/year. Thus, the contribution of NTFPs to household income amounted to 89.72%, indicating that NTFPs are the main source of livelihood for HKm farmers in this area.